Isolation of Oxo-degradable Polyethylene Degrading-Bacteria of Benowo Landfill Soil Surabaya - MUKAMTO MUKAMTO; YUNI SRI RAHAYU; LISA LISDIANA; HARDANING PRANAMUDA (Indonesian Society for microbiology, 2015)
The widespread consumption of oxo-degradable polyethylene plastics in Indonesia is potentially cause pollution. This problem can be overcome by utilize plastic degrading-bacteria as degradation agent. The present study aims to isolate and characterize of oxo-degradable polyethylene degrading-bacteria from Benowo landfill soil Surabaya. Isolation and screening was done by the culture technique and clear zone method. Total abundance of bacteria was calculated based on the Total Plate Count method. Bacterial colonies screening was done based on morphological characteristics and the diameter of clear zone. Four isolates with the largest diameter of clear zone were futher characterized based on cell morphology and physiology biochemistry characters. The results showed the average of total abundance of oxo-degradable polyethylene degrading-bacteria of Benowo landfill was 1.28 x 104 CFU g-1. The four of twelve isolates with the largest diameter of clear zone was indicated the highest degradation capability, that were isolates A221 (0.7 cm), A231 (1 cm), A232 (0.6 cm), and C231 (1.3 cm). Colony morphology characteristics of four isolates were generally shape of circular and irregular; margin of entire and lobate; elevation of flat; optics of opaque; and pigmentation of yellow, greenish and cream. These four isolates were Gram negative with the shape bacilli and cell size range of 3-4 Î¼m. Physiological and biochemical characteristics among the four isolates were resistant to acidic conditions; non-motile; produce catalase enzyme except A231; capable to reduce glucose and mannitol; uncapable to reduce lactose; capable to produce acids, except A232; produce of 2.3-butanediol; unable reduce sodium malonate; and capable to reduce nitrate, except A232 and C231; as well as producing hydrogen sulfide except A221 and A232. The four isolates has similar properties with the genus Mycobacterium.